Recent Pathophysiological Aspects of Peyronie’s Disease: Role of Free Radicals, Rationale, and Therapeutic Implications for Antioxidant Treatment—Literature Review - Gianni Paulis; Gennaro Romano; Luca Paulis; Davide Barletta (Advances in Urology)
Peyronie’s disease (PD) is a chronic inflammation of tunica albuginea of the corpora cavernosa that causes an inelastic plaque resulting in penis deformation. Although its etiology is not completely known, there is general consensus that PD is genetically transmitted and secondary to penile trauma. In recent years, numerous studies demonstrated the role played by oxidative stress in PD pathogenesis, and other studies have described successful use of antioxidants in PD treatment. Oxidative stress is an integral part of this disease, influencing its progression. In the early stages of PD, the inflammatory infiltrate cells produce high quantities of free radicals and proinflammatory and profibrotic cytokines, with consequent activation of transcription factor NF-κB. While conservative therapies commonly used in the early stages of PD include oral substances (Potaba, tamoxifen, colchicine, and vitamin E), intralesional treatment (verapamil, interferon, steroids, and more recently collagenase clostridium histolyticum-Xiaflex), and local physical treatment (iontophoresis, extracorporeal shock wave therapy, and penile extender), the significant results obtained by emerging treatments with the antioxidants cited in this article suggest these therapeutic agents interfere at several levels with the disease’s pathogenetic mechanisms. Antioxidants therapy outcomes are interesting for good clinical practice and also confirm the fundamental role played by oxidative stress in PD.